Cedar forests, cedar ships : allure, lore, and metaphor in the Mediterranean Near East - Rich, Sara A., (Archaeopress, 2016)
It is commonly recognized that the Cedars of Lebanon were prized in the ancient world, but how can the complex archaeological role of the Cedrus genus be articulated in terms that go beyond its interactions with humans alone?